Tricalcium phosphate (-containing) biomaterials in the treatment of periodontal infra-bony defects: A systematic review and meta-analysis. (November 2021) - Liu, Chun Ching; Solderer, Alex; Heumann, Christian; Attin, Thomas; Schmidlin, Patrick R.
Abstract: Objectives: This study aimed to investigate the additional clinical benefit of tricalcium phosphate (TCP) (-containing) biomaterials compared to open flap debridement (OFD) in periodontal infra-bony defects. Data: A literature search was conducted in Pubmed, Embase and Cochrane library for entries published up to 14th July 2021. All randomized controlled trials (RCTs) that compared a TCP (-containing) material with OFD and studies that assessed a beta-TCP group alone, with vertical defect sites with PPD of ≥ 6 mm and/or presence of infra-bony defects of ≥ 3 mm and a minimum follow-up of 6 months were included. Risk of bias was assessed with the Oxford scale. The random-effects (RE) model was synthesized as differences between weighted average (MD) for probing pocket depth (PPD) and clinical attachment level (CAL) between TCP and OFD groups. An RE analysis was also performed for the beta-TCP group alone. Study selection: Data from 16 RCTs were included in the analysis. Six studies that represented 151 patients and sites were selected for meta-analysis. The overall MD with 95% CI at 6 months was calculated to be -0.47 [-0.83, -0.12; P  = 0.0087] and -1.06 [-1.67, -0.46; P  = 0.0006] for PPD and CAL, respectively. Whereas MD at 12 months for PPD and CAL was -0.89 [-1.54, -0.23; P  = 0.0078] and -1.25 [-1.85, -0.66; P <0.0001], respectively. All results were in favor of TCP (-containing) group over OFD. Conclusions: The results of the study suggest that the use of a TCP (-containing) material may have the potential for additional clinical improvement in PPD and CAL compared with OFD in infra-bony defects, given the limitations of the included evidence. Clinical significance: The use of TCP as a bone graft substitute is becoming increasingly common. Therefore, it would be advantageous if an adjunctive benefit in the regeneration of infra-bony defects could be demonstrated to facilitate material selection.